Mortality Rate and Years of Life Lost due to Hypertension in the South of Iran between 2004 and 2019: A Population-Based Study - Alireza Mirahmadizadeh; Mohebat Vali; Jafar Hassanzadeh; Seyed Parsa Dehghani; Ahmadreza Razeghi; Habibollah Azarbakhsh (International Journal of Hypertension)
Introduction. Hypertension is known worldwide as a preventable significant risk factor for cardiovascular diseases and their mortality. This study was designed to determine the mortality rate and years of life lost (YLL) due to hypertension in Fars Province. Method. In this cross-sectional study, we extracted all death reports due to hypertension based on age, gender, and the year of death based on ICD-10 from the EDRS system (Electronic Death Registration System). The YLL analysis due to premature death related to hypertension was executed by the 2015 YLL template from WHO in EXCEL 2016 software. To examine the trend of crude and standardized mortality rates and YLL rates for different years, joinpoint regression was used based on the log-linear model. Results. In the 16 years that the study was done (2004–2019), 13443 death cases occurred in the Fars Province, 51.0% of which (6859 cases) were in females and 48.5% (6515 cases) of which were in the 80+ age group. Total YLL due to hypertension in these 16 years of study was 61,344 (1.9 per 1000) in males, 64,903 (2.1 per 1000) in females, and 126,247 (2.0 in 1000) in both genders. According to the joinpoint regression analysis, the 16-year trend of YLL rate due to premature mortality was increasing: the average annual percent change (AAPC) was 4.9% (95% CI −2.6 to 12.85, p value=0.205) for males and 8.4% (95% CI 5.2 to 11.7, p value <0.001) for females. Conclusion. Considering the increasing trend in crude and standardized mortality rates and YLL due to hypertension, it is important for policymakers and decision makers of Health Policy Centers to promote and inform people about the importance of hypertension control and to familiarize them with proper, preventive interventions such as the importance of a healthy diet, routine physical activity, and routine learning programs for different groups in the society especially for people at a higher risk of hypertension.